Análise de desempenho de sistemas OFDM cooperativos DF com amplificadores de potência não lineares - Sousa, Diego Aguiar (2013)
In the lastest years, orthogonal frequency division multiplexing (OFDM) has been widely associated with cooperative radio techniques. In this context, a study about the effects of the high peak-to-average power ratio (PAPR), a well known OFDM problem, has a great relevance. This dissertation proposes an analytical formulation for the outage probability and symbol error rate (SER) in a cooperative OFDM system with one relay using fixed and selective decode-and-forward (DF) retransmission protocols, considering the nonlinear distortions inserted by the source and relay power amplifiers (PA). In the considered model, the receiver exploits the signal received directly from the source as well as the the signal transmitted through the relay using the maximum ratio combing (MRC) technique. The effects of the nonlinearities in the considered system are studied by verifying their impact in the system diversity order and by analysing how much they deteriorate the received signal. The presented analysis applies to any kind of memoryless amplifier. The proposed theoretical expressions are validated by means of computer simulations in different scenarios.